2022
DOI: 10.17267/2238-2704rpf.2022.e4799
|View full text |Cite
|
Sign up to set email alerts
|

Comparando o efeito da liberação miofascial e técnica de energia muscular na ângulo e cefaleia em pacientes com cefaleia tensional

Abstract: INTRODUÇÃO: Cefaleias tensionais podem ser induzidas pela postura da cabeça para frente, e há uma grande quantidade de evidências disponíveis para o manejo de cefaleias crônicas. Os dados suportam o uso de abordagens de terapia manual para gerenciar dores de cabeça do tipo tensional. Devido à postura anterior da cabeça, a região do músculo suboccipital torna-se curta, resultando em aumento da lordose e dor no pescoço. Pacientes com uma postura de cabeça ainda mais para frente têm um ângulo craniovertebral meno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Thus, any malfunction of this muscle can influence balance while using a bike. It has also been found that hamstring muscle strain is one of the risk factors leading to low back discomfort in patients, particularly those who drive constantly for hours 8 . The flexibility of the hamstring when bending forward affects the angle and range of motion (ROM) of the pelvis and thoracic region 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, any malfunction of this muscle can influence balance while using a bike. It has also been found that hamstring muscle strain is one of the risk factors leading to low back discomfort in patients, particularly those who drive constantly for hours 8 . The flexibility of the hamstring when bending forward affects the angle and range of motion (ROM) of the pelvis and thoracic region 9 .…”
Section: Introductionmentioning
confidence: 99%
“…MET is an osteopathic tissue manipulation technique involving precision-directed and controlled active isometric and isotonic contractions to enhance musculoskeletal function and reduce pain. MET can be used to lengthen and strengthen muscles, improve fluid dynamics, minimize surrounding edema, and mobilize a restricted joint 8 . In addition, the self-assisted myofascial release technique (SMFR) is another treatment choice used by most physiotherapists.…”
Section: Introductionmentioning
confidence: 99%